Meat Intake Is Associated with a Higher Risk of Ulcerative Colitis in a Large European Prospective Cohort Studyø. (9th April 2022) - Dong, Catherine; Chan, Simon S M; Jantchou, Prevost; Racine, Antoine; Oldenburg, Bas; Weiderpass, Elisabete; Heath, Alicia K; Tong, Tammy Y N; Tjønneland, Anne; Kyrø, Cecilie; Bueno de Mesquita, Bas; Kaaks, Rudolf; et al.
Abstract: Background and Aims: We aimed to investigate the association between protein intake and risk of inflammatory bowel disease [IBD] in the European Prospective Investigation into Cancer and Nutrition. Methods: A total of 413 593 participants from eight European countries were included. Dietary data were collected at baseline from validated food frequency questionnaires. Dietary data were calibrated to correct errors in measures related to each country-specific questionnaire. Associations between proteins [total, animal, and vegetable] or food sources of animal proteins, and IBD risk were estimated by Cox proportional hazard models. Results: After a mean follow-up of 16 years, 177 patients with Crohn's disease [CD] and 418 with ulcerative colitis [UC], were identified. There was no association between total protein, animal protein, or vegetable protein intakes and CD or UC risks. Total meat and red meat intakes were associated with UC risk (hazard ratio [HR] for the 4th vs 1st quartile = 1.40, 95% confidence interval [CI] = 0.99-1.98, p -trend = 0.01; and 1.61, 95% CI = 1.10-2.36, p -trend = 0.007, respectively]. There was no association between other food sources of animal protein [processed meat, fish, shellfish, eggs, poultry] and UC. We found no association between food sources of animal proteins and CD risk. Conclusions: Meat and red meat consumptions are associated with higher risks of UC. These results support dietary counselling of low meat intake in people at high-risk of IBD. Graphical Abstract: